2021
DOI: 10.3390/biom11030386
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the cl-Par-4 Tumor Suppressor as a Function of Ionic Environment

Abstract: Prostate apoptosis response-4 (Par-4) is a proapoptotic tumor suppressor protein that has been linked to a large number of cancers. This 38 kilodalton (kDa) protein has been shown to be predominantly intrinsically disordered in vitro. In vivo, Par-4 is cleaved by caspase-3 at Asp-131 to generate the 25 kDa functionally active cleaved Par-4 protein (cl-Par-4) that inhibits NF-κB-mediated cell survival pathways and causes selective apoptosis in tumor cells. Here, we have employed circular dichroism (CD) spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Expression and purification of D313K were conducted following the established procedure for WT cl-Par-4 [ 37 , 39 ]. In brief, BL21 (DE3) codon plus E. coli cells, transformed with the codon-optimized mutant construct D313K, were cultured in Luria-Bertani (LB) medium supplemented with ampicillin for selective growth at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression and purification of D313K were conducted following the established procedure for WT cl-Par-4 [ 37 , 39 ]. In brief, BL21 (DE3) codon plus E. coli cells, transformed with the codon-optimized mutant construct D313K, were cultured in Luria-Bertani (LB) medium supplemented with ampicillin for selective growth at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…We previously found that cl-Par-4 at pH 7.0 requires a high salt concentration to form compact helical tetramers [ 38 , 39 ]. For NMR analysis, high salt and tetramer formation are problematic in terms of the signal-to-noise ratio and line width.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The work presented by Raut and colleagues [15] investigated Par-4 (Prostate apoptosis response-4), a predominantly intrinsically disordered protein, acting as a tumoural suppressor that is capable of selectively inducing apoptosis in cancer cells while leaving healthy cells unaffected. The authors performed experimental studies, employing circular dichroism spectroscopy and dynamic light scattering to assess the effects of various monovalent and divalent salts upon the conformation of cl-Par-4 in vitro.…”
mentioning
confidence: 99%